FACTORS AFFECTING EXTERNAL AUDITOR CHANGES: A CASE STUDY ON INDONESIA CAPITAL MARKET FROM PERIODS 2010-2014 - Yoni Yogiswara; Made Sudarma (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
Concomitant with the economic growth, the development of companies in Indonesia is increasing as well. Moreover the company is obliged to prepare and present their financial statements, and it should be open and known by relevant parties, considering their related parties are not only internal parties but also external parties such as investor, creditors, and stakeholders. This causes the role of auditors is needed by the parties who require reliable assurance, because independent auditor is the only credible independent party for those who want to get a reliable assurance. In line with those phenomenon, this research carried to prove the hypotheses used in previous research in determining the auditor change in Indonesia. This quantitative research which analyze Manufacture Company listed in Indonesia Capital Market from 2010 to 2014 as samples. And the prior year audit opinion, CPA’s firm size, management rotation, company’s growth and financial distress as independent variables. To do the hypotheses test, logistic regression test was conducted. Finally, the result shows that audit opinion has negative significant affect to auditor change and management rotation has positive significant effect to auditor change. Meanwhile, CPA’s firm size, ROA Change, and financial distress have negative yet significant effect to auditor change. Keywords : Audit, Auditor Change, Financial Distress, ROA Change, Prior Year Audit Opinion, Manufacture